Pengaruh Disiplin Kerja terhadap Kinerja Pegawai Kantor Walikota Sorong - Makisurat, Fenny Avelia; Kastanya, James; Timisela, Yanti M. (Attractive : Innovative Education Journal, 2022)
This study aims to analyze the effect of work discipline on the performance of the Sorong Mayor's Office. The data analysis method used is descriptive quantitative analysis. significant test through (t-test), using simple linear regression and coefficient of determination (R2). The population in this study were all employees at the Sorong Mayor's Office. A sample were 58. respondentsThe primary data obtained through interviews, the questionnaire and the study. Documentation. From the results of data processing simple linear regression analysis using the SPSS for windows version 25 program, the regression equation Y = 8.041 + 0.681X, the regression coefficient value of 0.875 means that every time there is a change and an addition of one percent in the Work Discipline variable, the Employee Performance variable will increase. of 0.681 if the Work Discipline variable is zero, then the employee's performance has a value of 8.041. The coefficient of determination test obtained R square 51.6%. it means that work discipline has an effect on employee performance by 51.6%. while the remaining 48.4% is influenced by other factors that are not analyzed in this study.The results of the t-test, where tcount 7.731> from ttable 1.6725, it can be said that the work discipline variable has a positive and significant effect on employee performance Keywords: Work Discipline, Employee Performance, Dicipline Employee